The 10th Distinguished Tun Abdul Razak Lecture: event guide / Ohio University, University Teknologi MARA (UiTM) and University Putra Malaysia (UPM) - United States, Ohio University; Malaysia, University Teknologi MARA; Malaysia, University Putra Malaysia (2018)
This Lecture is also an occasion to profile and celebrate the Tun Abdul Razak Chair establishment at Ohio University in 1980 by the Government of Malaysia through the Ministry of Education.